The value of blood lactate and lactate clearance rate in evaluating the prognosis of athletes with heat illness of varying degrees after high-intensity exercise - Yu, L.; Dong, X.; Li, H.; Mi, L. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Heat stroke, a severe heat illness with organ damage, is a major cause of cause irreparable organ damage and higher death rates among military persons and athletes.